Supplementation of Dietary Quercetin and Vitamin E Promotes the Intestinal Structure and Immune Barrier Integrity in Aged Breeder Hens - Amevor, Felix Kwame; Cui, Zhifu; Du, Xiaxia; Ning, Zifan; Deng, Xun; Xu, Dan; Shu, Gang; Wu, Youhao; Cao, Xueqing; Shuo, Wei; Tian, Yaofu; Li, Diyan; et al. (Frontiers in Immunology, 2022)
In aged animals, the physiological functions of the gastrointestinal tract (GIT) are reduced. Dietary intervention is necessary to re-activate GIT functions. The objective of this study was to investigate the impacts of dietary combination of quercetin (Q) and vitamin E (VE) on the intestinal structure and barrier integrity in aged breeder chickens. A sum of 400 (65-wks-old) Tianfu breeder hens were randomly allotted into four (4) groups with four (4) replicates, and fed with basal diet; basal diet supplemented with 0.4g/kg of Q; basal diet supplemented with 0.2g/kg of VE; and basal diet supplemented with the combination of Q (0.4 g/kg) and VE (0.2 g/kg) for 14 weeks. At the end of the 14th week, serum and gut segments were collected from eight hens per group for analyses. The results showed that Q+VE exerted synergistic effects on intestinal morphology by promoting villi height and crypt depth (P < 0.05), as well as mitigated the intestinal inflammatory damage of the aged hens, but decreased the concentration of serum D-lactate and diamine oxidase; and increased the levels of secretory immunoglobulin A (sIgA) and Mucin-2 mRNA (P < 0.05). Furthermore, the mRNA expression of intestinal tight junction proteins including occludin, ZO1, and claudin-1 was increased by Q+VE (P < 0.05). Moreover, Q+VE decreased the mRNA expression of the pro-inflammatory genes (TNF-α, IL-6, and IL-1β), and increased the expression of anti-inflammatory genes (IL-10 and IL-4) (P < 0.05). These results were consistent with the mRNA expression of Bax and Bcl-2. In addition, Q+VE protected the small intestinal tract from oxidative damage by increasing the levels of superoxide dismutase, total antioxidant capacity, glutathione peroxidase, catalase (P < 0.05), and the mRNA expression of SOD1 and GPx-2. However, Q+VE decreased malondialdehyde levels in the intestine compared to the control (P < 0.05). These results indicated that dietary Q+VE improved intestinal function in aged breeder hens, by protecting the intestinal structure and integrity. Therefore, Q+VE could act as an anti-aging agent to elevate the physiological functions of the small intestine in chickens.